PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA ASN KANTOR KEMENAG KABUPATEN SITUBONDO - M. Fachri Farriyansyah; Mohammad Yahya Arief; Muhammad Iqbal Anshory (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of compensation, work discipline, and work environment on employee performance, with job satisfaction as an intervening variable at Puskesmas Jangkar in Situbondo. Employee performance is a crucial factor in achieving organizational goals, influenced by both financial and non-financial aspects. This research employed a quantitative approach, using questionnaires distributed to civil servant employees (ASN). Data analysis was conducted using the Structural Equation Modeling (SEM) technique with the help of SmartPLS software. The results indicate that compensation has a positive but not significant effect on job satisfaction, suggesting that increased compensation does not directly improve employees’ job satisfaction. On the other hand, work discipline and work environment significantly affect both job satisfaction and employee performance. Furthermore, job satisfaction has a significant impact on performance. These findings highlight that non-financial factors such as discipline and a supportive work environment play a critical role in enhancing job satisfaction and boosting employee performance. The implications of this study suggest that the management of Puskesmas Jangkar should prioritize the creation of a positive work environment and the enforcement of work discipline as strategies to improve overall employee performance.